Effect of Guanxin V in animal model of acute myocardial infarction - Xiaoxiao Zhang; Changle Shao; Songyi Cheng; Yao Zhu; Bo Liang; Ning Gu (BMC, 2021)
Abstract Background Acute myocardial infarction (AMI) is the most serious and lethal manifestation of coronary heart disease worldwide, presenting extremely high disability and mortality. Our previous studies have shown that Guanxin V (GXV) could significantly improve the cardiac function and the blood flow dynamics, and reduce serum levels of inflammatory factors in AMI rats, thus triggering ventricular remodeling (VR) at post-AMI. Methods An in vivo AMI model was established in Syrian hamsters by performing the ligation of the left anterior descending coronary artery. Syrian hamsters were randomly divided into four groups, namely Sham operation group (n = 12), AMI group (n = 12), GXV group (GXV 6 g/Kg/d, n = 12), and Tranilast group (Tra 105 mg/Kg/d, n = 12). Drug intervention was conducted for consecutive 8 weeks. Relative biological indicators were measured in the 4th and 8th week, respectively. Results Cardiac functions were improved, and the infarcted size and heart weight index were limited in Syrian hamsters of GXV and Tra groups compared with those in AMI group. Furthermore, GXV was able to decrease the number of mast cells and chymase level in Syrian hamsters with AMI. Administration of GXV remarkably inactivated the renin-angiotension-aldosterone system, and alleviated myocardial fibrosis and cardiomyocyte apoptosis, thus slowing down VR at post-AMI. Conclusion GXV slows down the process of VR at post-AMI by reducing chymase level and mast cells number, as well as inactivating the reninangiotension-aldosterone system..